PENGARUH PENGGUNAAN SISTEM COMPUTER ASSISTED TEST PADA EFISIENSI BIAYA DAN AKUNTABILITAS PUBLIKASIAN HASIL (STUDI PADA TES SELEKSI PENERIMAAN CPNS DI KABUPATEN JEMBRANA DAN KARANGASEM TAHUN 2014) - Buana, I Ketut; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.11.TAHUN 2015, 2016)
Selection of the CPNS (Public Official Candidates) by using the Computer Answer Sheet results is prone to manipulation of data physically.National Civil Service Agency introduces Computer Assisted Test (CAT) System since 2009. Nationally, the CAT system is a must to use on 2014, including the selection CPNS Jembrana and Karangasem Regency. This research examines an influence of the use of the CAT system variables towards cost efficiency and accountability of the publication of results. The number of respondents in this research is 1,825 people which qualified the respondent's purposive sampling. Q uestionnaire distributed to participants of the selection shortly after a basic competency tests in the CAT Station at Region X of BKN Office in Denpasar. Analytical techniques used are simple linear regression analysis. The result of this research determines that the use of the CAT system has positive influences on cost efficiencies and also has a positive influence on accountability of the publication of results. By this research can be concluded that the use of the CAT syste m is effective and efficient . In future the intuition sugested to develop and use CAT system widely.
Keywords: CAT, Cost Efficiency, Accountability